Serodiagnosis Profiling of Anti SARS-CoV-2 Among Blood Donor Surabaya Indonesia - Woelansari, Evy Diah; Sasongkowati, Retno; Christiyaningsih, Juliana (Poltekita : Jurnal Ilmu Kesehatan, 2024)
SARS-CoV-2 antibody detection is used as a response to natural infection and vaccination. Antibody response is very important in viral seroepidemiology and the potential role of antibodies in disease. This study was to determine serodiagnosis anti SARS-CoV-2 among blood donor Surabaya detect antibodies with protein molecular weight as serodiagnosis and immune response to SARS-CoV-2 in donors in Surabaya. The research used in this study was exploratory descriptive design. Samples from blood donors as many as 150 samples at UTD PMI Surabaya. The examination was carried out by detecting IgG SARS-CoV-2 antibodies ELISA method and followed by protein molecular weight examination SDS-PAGE method (semi-log The results of the ELISA method antibody examination showed that 67 people had IgG antibody titers against SARS-CoV2 (44.7%) and 83 people were negative (55.3%) (COI: 0.1535-0.1569). Furthermore, the results of the SDS- PAGE method examination obtained the average molecular weight in band 1: 49.73 kDA, band 2: 25.26 kDA; band 3: 19.63.4 kDA; band 4: 12.35 kDA and band 5: 7.33 kDA. There were IgG antibody of SARS CoV-2 in blood donor Surabaya meanwhile from protein screening results we could not find protein of spike SARS-CoV-2 in Blood donor Surabaya.